Penentuan Sisa Umur Pakai Struktur Conveyor D pada Tambang Batubara PT XYZ di Kabupaten Tapin, Provinsi Kalimantan Selatan - Padli Ahmad Wijaya Kusuma; Elfida Moralista; Yuliadi (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Conveyor is a means of transportation that is generally used in the coal mining industry which serves to move coal. The structure of the conveyor is made of carbon steel which is prone to corrosion and one of the causes is interacting with the environment. Therefore, it is necessary to monitor and control corrosion in order to achieve the design life of the conveyor structure.The research was conducted on a 90 meter long conveyor structure which is divided into 3 segments with 25 test points. This study aims to determine the type of corrosion, corrosion control, corrosion rate and the remaining service life of the conveyor structure.The research methodology is thickness reduction measurement. The instrument used for measurement is ultrasonic thickness gauge TT 130. The research location has an air temperature ranging from 26.3°C-28.1°C with annual rainfall of 2,219,782 mm/year and relative humidity of 90.9%. .Based on the results of data processing, it is found that the type of corrosion that occurs in the conveyor structure is uniform corrosion. Corrosion control is carried out using a coating method with a three layer system with the coating used in the form of a Seaguard 5000 primer coating, an intermediate sherglass FF coating and aliphatic acrylic modified polyurethane top coating. The corrosion rate that occurs in the conveyor structure ranges from 0.1688-0.3100 mm/year with a good category based on the relative corrosion resistance of steel. The service life of the conveyor structure is 8 years with the remaining service life ranging from 5.75 years to 9.76 years. Thus, there are 28% test points that are predicted not to reach its design life of 15 years. Abstrak. Conveyor adalah alat transportasi yang umumnya digunakan di industri pertambangan batubara yang berfungsi untuk memindahkan batubara. Struktur conveyor terbuat dari bahan dasar baja karbon yang rawan mengalami korosi dan salah satu penyebabnya adalah berinteraksi dengan lingkungan. Oleh karena itu perlu dilakukan kegiatan monitoring dan pengendalian korosi agar dapat mencapai umur desain dari struktur conveyor. Penelitian dilakukan pada struktur conveyor sepanjang 90 meter yang terbagi menjadi 3 segmen dengan 25 test point. Penelitian bertujuan untuk mengetahui jenis korosi, pengendalian korosi, laju korosi dan sisa umur pakai struktur conveyor. Metodologi penelitian adalah pengukuran pengurangan ketebalan. Alat yang digunakan untuk pengukuran adalah ultrasonic thickness gauge TT 130. Lokasi penelitian memiliki temperatur udara berkisar antara 26,3°C-28,1°C dengan curah hujan per tahun sebesar 2.219,782 mm/tahun dan kelembaban relatif sebesar 90,9%. Berdasarkan hasil pengolahan data maka didapatkan jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Pengendalian korosi yang dilakukan menggunakan metode coating dengan sistem three layer dengan coating yang digunakan berupa primer coating Seaguard 5000, intermediate coating sherglass FF dan top coating aliphatic acrylic modified polyurethane. Laju korosi yang terjadi pada struktur conveyor berkisar antara 0,1688-0,3100 mm/tahun dengan kategori good berdasarkan ketahanan korosi relatif baja. Umur pakai struktur conveyor 8 tahun dengan sisa umur pakai berkisar antara 5,75 tahun sampai 9,76 tahun. Dengan demikian maka terdapat 28% test point yang diprediksi tidak dapat mencapai umur desain nya yaitu 15 tahun.